Interest Rates and Inflation: Knives Out - Blair Fix (Economics from the Top Down, 2023)
If you're just tuning in, I've spent the last few months debunking some common misconceptions about inflation: Is inflation a uniform increase in prices? No. Inflation is wildly differential. Is inflation driven by an `over-heated' economy? No. Inflation tends to come with economic stagnation. Do higher interest rates reduce inflation? No. Higher interest rates are associated with higher inflation. As expected, the last claim put mainstream economists into war mode. You see, the belief that interest rates down-regulate inflation has come to be sacred. So by scrutinizing this idea with evidence, I was effectively torching an effigy of the pope. (Novelist Cory Doctorow helped fan the flames by writing an incendiary essay about my research.) And so I spent a `fun' week on Twitter being bombarded by econo-scorn. Now back to science. When I published `A Test of Monetary Faith', I had more evidence in the pipelines — evidence that debunks the idea that interest rates down-regulate inflation. In this post, I'll wade through the data. The take-home message is clear: when we look at the World Bank database, there is no evidence that higher interest rates down-regulate inflation. If anything, the evidence suggests that rate hikes make inflation worse. But before we get to the data, I'll respond to some of the more cogent criticisms that economist hurled my way.
Keywords: E31; E43; F4; E52; 330; interest rates; inflation; monetarism; monetary policy